2016
DOI: 10.1002/clc.22592
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density is associated with left ventricular diastolic function in women

Abstract: Background Low bone mineral density (BMD) and left ventricular (LV) diastolic function are associated with heart failure. However, little is known about the association between BMD and LV diastolic function. Hypothesis BMD is independently related to LV diastolic function in women. Methods We conducted a cross‐sectional study of 432 women. Brachial‐ankle pulse wave velocity (baPWV) and BMD measurements were performed. LV diastolic function and structure were assessed by echocardiographic examination. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
4
4
0
1
Order By: Relevance
“…In women with CAD, in parallel with the decrease in BMD state, grade 1 diastolic dysfunction of the left ventricle was more common, which was verified by the Ve/Va ratio tendency to decrease and LV isovulumic relaxation time slowdown lengthening, the significant DT increase if compared to the patients with CAD and normal BMD state. The data obtained coincide with the results of Wang R. et al (2016) [15]. Thus, in the Wang's study, BMD loss was identified as an independent predictor of LV diastolic dysfunction, which can be explained by the effect of chronic inflammation with the hyperproduction of cytokines, growth factors, prostanoids, nitric oxide, and the development of oxidative stress in the combination with the endothelial dysfunction [15].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In women with CAD, in parallel with the decrease in BMD state, grade 1 diastolic dysfunction of the left ventricle was more common, which was verified by the Ve/Va ratio tendency to decrease and LV isovulumic relaxation time slowdown lengthening, the significant DT increase if compared to the patients with CAD and normal BMD state. The data obtained coincide with the results of Wang R. et al (2016) [15]. Thus, in the Wang's study, BMD loss was identified as an independent predictor of LV diastolic dysfunction, which can be explained by the effect of chronic inflammation with the hyperproduction of cytokines, growth factors, prostanoids, nitric oxide, and the development of oxidative stress in the combination with the endothelial dysfunction [15].…”
Section: Discussionsupporting
confidence: 84%
“…The data obtained coincide with the results of Wang R. et al (2016) [15]. Thus, in the Wang's study, BMD loss was identified as an independent predictor of LV diastolic dysfunction, which can be explained by the effect of chronic inflammation with the hyperproduction of cytokines, growth factors, prostanoids, nitric oxide, and the development of oxidative stress in the combination with the endothelial dysfunction [15].…”
Section: Discussionsupporting
confidence: 84%
“…Leptin may be a connecting factor between osteoporosis and CHF. Our study has confirmed the already known fact of leptin level reduction in CHF patients, probably due to the activation of catabolic processes during heart failure and malnutrition [21]. However, in our patient group, leptin reduction was significantly associated with lower BMD.…”
Section: Discussionsupporting
confidence: 90%
“…Более заметная потеря МПКТ у женщин объясняется, в первую очередь, снижением уровня эстрогенов в постменопаузе. Эстрогены играют важ-ную роль в метаболизме костной ткани как непосред-ственно, стимулируя, прежде всего, функцию остео-бластов, так и косвенно за счет влияния на провоспа-лительные цитокины и окисленные липиды [12,20]. Андрогены тоже могут оказывать позитивное влия-ние на минеральную плотность костной ткани, хотя и не столь отчетливое, как эстрогены [12].…”
Section: Discussionunclassified